Cultural and linguistic affinities amongst Meitei-Sizang-Thadou - Sarangthem, Bobita; Lhouvum, Lhingneilam (Nepalese Linguistics, 2019)
This paper attempts to highlight the cultural and linguistic affinities amongst Meitei, Sizang and Thadou people. The data are collected from the field works in Imphal (Manipur, India), Tamu (Sagaing division of Myanmar) and Diphu (KarbiAnglong of Assam, India) for Meitei, Sizang, and Thadou respectively. Linguistically, Meitei, Sizang and Thadou share common Tibeto- Burman feature of SOV word order, agglutinative forms, sharing lexical cognates due to language contact. Culturally, these languages show some similarities; however, Thadou and Sizang are more similar. Nonetheless, languages have been a reflection of those cultural distinctions as well as their identities.